Plasticity in striatal dopamine release is governed by release-independent depression and the dopamine transporter - Mark D. Condon (Nature Portfolio, 2019)
Dopamine release in the striatum has important roles in action selection and in disorders such as Parkinson’s disease. The authors here show that short-term plasticity of dopamine release is strongly determined by axonal activation and dopamine transporters.